Development of Marine Tourism Based on Blue Economy Realizing Sustainable Development Goals (Case Study Of Teluk Penyu Beach Cilacap) - Jannah, Roikhatul; Hilyatin, Dewi Laela; Riyadi, Sugeng (Wealth: Journal of Islamic Banking and Finance, 2024)
The purpose of this study is to determine the concept of Blue Economy that has been applied in the development of marine tourism at the Teluk Penyu Beach Cilacap and the concept of Blue Economy at the Teluk Penyu Beach Cilacap in realizing Sustainable Development Goals. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. Data validity test using the source triangulation method and data analysis techniques with data collection, data reduction, data presentation, and conclusion drawing. The results of this study indicate that the development of marine tourism on the Teluk Penyu Beach Cilacap based on the Blue Economy is almost well implemented. This is seen from the implementation of three principles, namely nature’s efficiency, social inclusive, and multiple revenue that can realize several Sustainable Development Goals, namely the first goal without poverty, the second goal without hunger, the eighth goal of decent work and economic growth, the thirteenth goal of handling climate change, and the fourteenth goal of maintaining marine ecosystems. One principle that is still being worked on is the principle zero waste, which if it can be implemented properly can support the realization of the third goal of a healthy and prosperous life and the twelfth goal of responsible consumption and production which will be realized 2030